ANALISIS KAUSALITAS SEKTOR PARIWISATA, INDEKS PEMBANGUNAN MANUSIA DAN PERTUMBUHAN EKONOMI DI SUMATERA BARAT - Ismalisa Ismalisa; Ali Anis (Universitas Negeri Padang, 2019)
This study examines the causal relationship between the Tourism Sector, the Human Development Index and Economic Growth in West Sumatra. The data used in this study are panel data from 2012-2016 in 19 regencies / cities in West Sumatra, with documentation and library study data collection techniques obtained from relevant institutions and agencies. The variables used are the tourism sector, the human development index and economic growth. The research method used is to use the Panel Vector Autoreggression (PVAR) approach method which has several tests that must be carried out, namely: (1) Unit Root Test, (2) Cointegration Test, (3) Determination of Optimal Lag (4) Granger Causality Test ( 5) Impulse Response Fungtion (IRF) (6) Variance Decomposition (VD). The results of the study show that (1) There is unidirectional causality where the Human Development Index affects Tourism. (2) There is no causal relationship between the Tourism and Economic Growth sectors. (3) There is unidirectional causality where the Human Development Index affects Economic Growth. So, in this study there was no causality relationship between the three verifiable, but there was only one-way relationship.